Thirty Two Years of Weed Science Research in India (1950-1982) : A Bibliometric Study - Subbaiah, R. (Journal of Information and Knowledge, 1983)
An annotated bibliography, entitled "A Compendium of Indian Weed Science Research" Compendium and published in two volumes is used here as a source for the bibliometric analysis and the data is tabulated in five tables. The findings of the study reveals the subject year wise growth parameter of the subject under two heads viz. 1. Weeds and weedicides and 2. Weed control in crops. The source analysis identifies the sources of literature for this subject and projects the journals are the major sources of information for this subjects. It is revealed here that among the grey literature the conference proceedings are very important for this subject. The authorship analysis reveals the fact the collaborative research is predominant in this subject. Concluded stating that the findings of this study may be utilized by Scientists in designing their research projects in agriculture.